Analysis on the Influence of Employer Branding Strategies with the Desires of Generation Z to Attract Potential Talent in the Start-Up Company: A Case Study of Andalin - Ferdian Adyaksa, Fahreza; Nurlaela Arief, Neneng (Green Publisher Indonesia, 2024)
The purpose of the research is to understand the factors that affect employer branding, particularly in the context of Generation Z employees in startup companies. Startups have emerged as a prominent career option for Generation Z in the current globalization era, due to their innovative and dynamic work environments. The goal of this study is to determine which aspects of employer attractiveness align with the aspirations and values of Generation Z, specifically analyzing PT Eximku Teknologi Indonesia (Andalin). The study used a qualitative methodology, involving in-depth interviews with internal Andalin and external startup employees. The purpose of the data collection is to identify how employees vary in their responses to the various aspects of employer attractiveness, such as Social Value, Development Value, Application Value, Safety Value, and Economic Value. According to the study, Andalin employees are largely satisfied on most criteria except Economic Value, where some respondents believe their workload is not appropriately provided. External respondents are dissatisfied with most characteristics, except for social, developmental, and economic values, demonstrating a lack of organizational belonging and long-term job stability in startups. Notable results indicate that social media efficiently showcases the working environment to Generation Z and attracts their attention, demonstrating how it is so important for employer branding. Another suggested strategy to increase awareness of the company's culture, vision, mission, and core values of the company is to improve the career website. Furthermore, offering complimentary educational or developing skills courses is suggested as an efficient way of underlying continuous development within the organization, which results in attracting potential employees.